Effects of crisis severity and crisis response strategies on post-crisis organizational reputation - Choi, Sera, author; Kim, Jangyul, advisor; Park, Youngeun, committee member; Long, Ziyu, committee member (Colorado State University. Libraries, 2019)
Using situational crisis communication theory (SCCT), this study investigates the impact of crisis severity and crisis response strategies on post-crisis organizational reputation within the field of crisis communication. In the experiments, 289 respondents participated in a 2 (crisis severity: low vs high) x 2 (crisis response strategy: match vs mismatch) between-subjects factorial design. The results show that in the case of high crisis severity, a matched crisis response strategy positively influenced post-crisis organizational reputation as compared to a mismatched crisis response strategy. However, in the case of low crisis severity, there was no impact of a matched or mismatched crisis response strategy on organizational reputation. The study discusses its theoretical and empirical implications and limitations.